PENGARUH PENAMBAHAN CAMPURAN SEMEN DAN ABU SEKAM PADI TERHADAP STABILISASI TANAH PADA RUAS JALAN BUDI UTOMO I - Olandri Wijaya; Mawardi Mawardi; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2019)
Research on the Effect of Mixed Addition of Cement And rice husk ash Against and Stabilization on Roads Budi Utomo I aims to determine the effect of Addition of Cement And rice husk ash and to finding the optimal mix levels of Addition of Cement And rice husk for land Stabilization. Tests conducted at the Laboratory of Engineering, University of Bengkulu and the types of tests as follows: natural water content, specific gravity, sieve analysis, atterberg limits, standard proctor,and CBR (California Bearing Ratio) laboratories. Based on laboratory testing, native land in Jalan Budi Utomo I was clay with high plasticity After testing the original soil coupled with a mixture of cement and rice husk ash obtained optimum results occur at levels of 12 % of the 4%, 8%, dan 12% variations. The following test results with a mixture of cement and rice husk ash with levels 12 % : on the CBR laboratories testing provide CBR value increase up to 148.42 % of the original soil CBR by weight of the dry contents increased up to 3.846 % of the dry weight of the contents of the original soil. The optimum moisture content decreased to 13.754 % of the original soil optimum water content, whereas soil plasticity index dropped to 50.084 % of the original soil plasticity index, and the specific gravity value of the land increased to 1.923 % of theoriginal soil. Improved stability of the soil caused by cement and rice husk ash containing silica elements where this element has a very large contribution as an adhesive and can harden by reaction with water so as to increase the strength of the soil stabilization.